Sosialisasi Pemanfaatan Hasil Hutan Bukan Kayu (HHBK) Sebagai Salah Satu Bentuk Pengelolaan KHDTK Kota Palangka Raya - Nanang Hanafi; Fahruni Fahruni; Siti Maimunah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Socialization of non-timber forest product utilization as one form of the management of forest area with special purpose of Palangka Raya City is implemented and centered in meeting hall of Mungku Baru sub-distict of Rakumpit of Palangka Raya city. The socialization was conducted using the funding of fiscal inthe year of 2015. The purpose of community service is creating of awareness and participation of the people around the forest area with special purpose to take care of and utilize the forest products sustainably; empowerment and participation of the people around forests aimed at achieving sustainable forest resource management and improving the welfare of forest villagers. The target community in this socialization activity is the community in Mungku Baru Sub-District of Rakumpit of Palangka Raya City with their economic activity mostly still depend on the existence of forests and fields around the forest. Non-timber forest products that can be utilized by the people such as gamor skin, honey, resin gum, and traditional medicines. Population of pilau/damar (Agathis borneensis) is very large in the forest education of University of Muhammadiyah Palangkaraya, which is spread naturally in an area of approximately 2,500 Ha. The resin copal can be harvested without damaging and cutting down trees, so that forest conservation can be maintained. University of Muhammadiyah Palangkaraya as one of the forest managers of education is committed to help the welfare of the villagers around the forest. Cooperation system offered is buying and selling resin copal.